Psoas and quadratus lumborum muscle asymmetry among elite Australian Football League players. Issue 8 (18th September 2008) - Hides, J; Fan, T; Stanton, W; Stanton, P; McMahon, K; Wilson, S
Abstract : Objective: In this study, asymmetry relative to the preferred kicking leg was determined if it exists for the psoas and quadratus lumborum muscles among elite Australian Football League (AFL) players. Design: AFL players were assessed at three time points from 2005 to 2007 (start of preseason, end of season and end of preseason training). MRI was used to determine the cross-sectional areas (CSAs) of the psoas and quadratus lumborum muscles at the L4–L5 vertebral level (psoas) and the L3–L4 vertebral level (quadratus lumborum). Setting: MRI was performed in a hospital setting. Participants: 54 professional AFL players were eligible to participate in this study. The number of subjects at each of the three time points was 36 for time 1 (T1 Nov 2005), 31 for time 2 (T2 Aug 2006) and 43 for time 3 (T3 Feb Mar 2007). Risk factors: The repeated measures factor in the analyses was "asymmetry", defined as "ipsilateral" or "contralateral" to preferred kicking leg. Number of injuries (coded as 0, 1, 2 or more) was also included as a risk factor. Main outcome measurements: The dependent variables were the CSAs of the psoas and quadratus lumborum muscles. Results: At all three time points, the CSA of the psoas muscle was significantly greater ipsilateral to the kicking leg, while the CSA of the quadratus lumborum muscle was significantly greater on the side contralateral to the kicking leg. Asymmetry in muscle size was not related to number of injuries. Conclusions: Asymmetry of the psoas and the quadratus lumborum muscles exists in elite AFL players.